Turkish local e-governments: A longitudinal study - (:unkn) unknown (ACADEMIC CONFERENCES LTD, 2007)
This article is based on a longitudinal exploratory study on the Turkish local e-governments as of September 2005 towards December 2006. 3228 Turkish local governments, in fact, the municipalities, constitute the sampling framework of this paper. The first part of the study took place in year 2005 and indicated that only 969 authorities went online. But in the second part, issued in the end of year 2006, gave rise to an amount of 1591 units online. The purpose of the second study was to explore the degree of change and how this change occurs in a certain time line among those authorities. Albeit some theoretical studies in this field, no research was held on local e-governments, particularly, in a longitudinal dimension in Turkey. That's why this study is unique in terms of covering the overall picture of the local level on e-government topic.
Keywords: Turkish e-Government (e-Government); Turkish local e-Government (e-Government); e-Municipality; e-Administration